A STUDY ON FEMALE LABOR FORCE PARTICIPATION IN INDIA - Dalal, Bhavya (PEOPLE: International Journal of Social Sciences, 2019)
The prediction of the neoclassical theory of HR suggests that increase in women’s education and literacy levels should generally result in a rise in the female labor force participation. As per the report of census in 2010, an inversely proportional relationship is been seen between them. This is also known as the U-shaped relationship that exists between the female literacy levels and workforce participation rates. In India, the Female Labor Force Participation (FLFP) rate remains extremely low at around 27% in comparison with the male labor force participation rate, which is around 79.9%. In the recent years, India has seen this trend of vanishing women workforce, which was opposite from what was predicted due to the increase in female literacy level. According to an IMF (International Monetary Fund) research it is predicted that the Indian economy can be boosted by 27%, if the participation of women in the workforce is increased to that of the level of men. India is still a patriarchal society, and even if the women are working, they are still expected to contribute to their household chores and duties. This creates a demotivating factor and lack of enthusiasm to overtake more responsibilities in their workplace. In spite of providing flexible work hours, the employees effectiveness in Indian working scenario is still judged on the basis of long working hours, the tendency to travel for work, which is not that much feasible for any middle class working female. The objective of this study is to identify certain cultural and structural factors that has contributed in this inversely proportional relationship.